Cognitive Function and Monoamine Neurotransmission in Schizophrenia: Evidence From Positron Emission Tomography Studies - Takano, Harumasa (Frontiers in Psychiatry, 2018)
Positron emission tomography (PET) is a non-invasive imaging technique used to assess various brain functions, including cerebral blood flow, glucose metabolism, and neurotransmission, in the living human brain. In particular, neurotransmission mediated by the monoamine neurotransmitters dopamine, serotonin, and norepinephrine, has been extensively examined using PET probes, which specifically bind to the monoamine receptors and transporters. This useful tool has revealed the pathophysiology of various psychiatric disorders, including schizophrenia, and the mechanisms of action of psychotropic drugs. Because monoamines are implicated in various cognitive processes such as memory and executive functions, some PET studies have directly investigated the associations between monoamine neurotransmission and cognitive functions in healthy individuals and patients with psychiatric disorders. In this mini review, I discuss the findings of PET studies that investigated monoamine neurotransmission under resting conditions, specifically focusing on cognitive functions in patients with schizophrenia under resting condition. With regard to the dopaminergic system, some studies have examined the association of dopamine D1 and D2/D3 receptors, dopamine transporters, and dopamine synthesis capacity with various cognitive functions in schizophrenia. With regard to the serotonergic system, 5-HT1A and 5-HT2A receptors have been studied in the context of cognitive functions in schizophrenia. Although relatively few PET studies have examined cognitive functions in patients with psychiatric disorders, these approaches can provide useful information on enhancing cognitive functions by administering drugs that modulate monoamine transmission. Moreover, another paradigm of techniques such as those exploring the release of neurotransmitters and further development of radiotracers for novel targets are warranted.